2015
DOI: 10.1037/adb0000094
|View full text |Cite
|
Sign up to set email alerts
|

Gateway to curiosity: Medical marijuana ads and intention and use during middle school.

Abstract: Over the past several years, medical marijuana has received increased attention in the media, and marijuana use has increased across the United States. Studies suggest that as marijuana has become more accessible and adults have become more tolerant regarding marijuana use, adolescents perceive marijuana as more beneficial and are more likely to use if they are living in an environment that is more tolerant of marijuana use. One factor that may influence adolescents’ perceptions about marijuana and marijuana u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
81
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 45 publications
5
81
0
5
Order By: Relevance
“…Exposure to marijuana advertisements through multiple channels further increased the odds of current marijuana use. Although this cross-sectional study precludes causal inferences, these results are consistent with the results of a previous study on middle school adolescents’ marijuana use in southern California (15). This study also confirmed that exposure to marijuana advertisements might have similar effects on adolescents’ marijuana use that exposures to advertisements for other substances (eg, alcohol, cigarettes, e-cigarettes) have on adolescents’ use of those substances.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Exposure to marijuana advertisements through multiple channels further increased the odds of current marijuana use. Although this cross-sectional study precludes causal inferences, these results are consistent with the results of a previous study on middle school adolescents’ marijuana use in southern California (15). This study also confirmed that exposure to marijuana advertisements might have similar effects on adolescents’ marijuana use that exposures to advertisements for other substances (eg, alcohol, cigarettes, e-cigarettes) have on adolescents’ use of those substances.…”
Section: Discussionsupporting
confidence: 89%
“…A few studies examined the relationship between exposure to marijuana advertisements and marijuana use among adolescents (1517). D’Amico and colleagues (15) surveyed 6th-, 7th-, and 8th-graders from 16 middle schools in southern California and found that exposure to medical marijuana advertisements was significantly associated with adolescents’ intention to use marijuana and their actual marijuana use 1 year later; the study, however, did not differentiate among channels of exposure (eg, stores, billboards, television, internet).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, marketing is a critical activity for commercial enterprises and is a key feature of this debate. Research has shown correlations between levels of cannabis consumption and both advertising (D'Amico, Miles, & Tucker, 2015;Room et al, 2010) and number of outlets (Freisthler & Gruenewald, A c c e p t e d M a n u s c r i p t 10 2014; Room, 2014). A recent study in California showed greater exposure to medical marijuana advertising was associated with higher probability of use among youth (D'Amico et al, 2015).…”
Section: March 22)mentioning
confidence: 99%
“…Research has shown correlations between levels of cannabis consumption and both advertising (D'Amico, Miles, & Tucker, 2015;Room et al, 2010) and number of outlets (Freisthler & Gruenewald, A c c e p t e d M a n u s c r i p t 10 2014; Room, 2014). A recent study in California showed greater exposure to medical marijuana advertising was associated with higher probability of use among youth (D'Amico et al, 2015). Traditional techniques of advertising are strictly limited in Colorado's recreational marijuana regulations including outright bans on advertisements that target children and may proceed only when evidence is provided documenting that less than 30% of the potential audience is under the age of 21.…”
Section: March 22)mentioning
confidence: 99%